Excessive screen time: Understanding its long-term impact on health and behavior - Inderpreet Kaur; Poonam Bakhetia (Emerging Trends in Personalized Medicines, 2025)
In today’s world, digital gadgets, like laptops, game consoles, smartphones, and televisions, are essential since they provide entertainment and convenience. However, their overuse has raised serious concerns regarding long-term health and social implications. This review investigates the extensive effects of excessive screen time on mental, physical, and social well-being, with a special emphasis on children and adolescents. The growing amount of time toddlers and preschoolers spend in front of screens is especially concerning since it undermines their social skills, causes behavioral issues, and interferes with their social development. Prolonged screen time negatively impacts physical health by disrupting sleep cycles, elevating the risk of obesity, and fostering a sedentary lifestyle. Psychologically, it leads to attention difficulties, increased anxiety, and a higher likelihood of depression, severely affecting emotional well-being. Socially, excessive screen use limits face-to-face interactions, weakens communication skills, and strains relationships, often resulting in a sense of isolation. Tackling these challenges necessitates a balanced approach to digital device use, especially among vulnerable groups. This article highlights the need to set clear screen time limits, encourage offline activities, and cultivate healthier habits. Additionally, it underscores the importance of future research in creating comprehensive guidelines and evidence-based policies to manage screen time effectively across various age groups. By recognizing the wide-ranging effects of excessive screen use, we can promote a healthier, more harmonious relationship with technology, leading to improved mental, physical, and social well-being for all.
Keywords: Screen Time; emotional well-being; mental and physical health; physical health; social health